Działalność nauczycielska Antoniego Gustawa Bema (1848–1902) we wspomnieniach wychowanków. Mistrzostwo pedagogiczne czy osobiste? - Kula, Ewa (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This article presents Anthony Gustav Bem, a junior high pedagogue who taught in Kielce and Warsaw, as he was remembered by his students. One of Bem’s pupil was Stefan Żeromski, a wellknown writer, and it is from Żeromski’s diaries that we learn about the teacher the most. Basing on quoted opinions, one might dare to say that Bem achieved in his profession a kind of personal mastery; it means that, in accordance with a definition coined by Peter M. Senge in "The Fifth Discipline", Bem treated his life as a creative activity, adopted proactive, not reactive, way of experiencing the world.
Keywords: Anthony Gustav Bem; creative activity; educational maestry; personal maestry; teacher